2021
DOI: 10.1038/s41598-021-92562-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal distribution patterns of Plutella xylostella (Lepidoptera: Plutellidae) in a fine-scale agricultural landscape based on geostatistical analysis

Abstract: A detailed knowledge on the spatial distribution of pests is crucial for predicting population outbreaks or developing control strategies and sustainable management plans. The diamondback moth, Plutella xylostella, is one of the most destructive pests of cruciferous crops worldwide. Despite the abundant research on the species’s ecology, little is known about the spatio-temporal pattern of P. xylostella in an agricultural landscape. Therefore, in this study, the spatial distribution of P. xylostella was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The relative variance in this study showed that plant growth stages preceding head maturation are particularly vulnerable to P. xylostella infestation, thus requiring consistent monitoring. This corroborates the findings of Li et al (2021) who reported that plant growth stages are an influential factor affecting the temporal distribution of P. xylostella .…”
Section: Discussionsupporting
confidence: 93%
“…The relative variance in this study showed that plant growth stages preceding head maturation are particularly vulnerable to P. xylostella infestation, thus requiring consistent monitoring. This corroborates the findings of Li et al (2021) who reported that plant growth stages are an influential factor affecting the temporal distribution of P. xylostella .…”
Section: Discussionsupporting
confidence: 93%
“…The diamondback moth (Plutella xylostella (Linnaeus)) is one of the most globally destructive and economically impactful pests of cruciferous vegetables [1], causing great losses in cruciferous plant production [2][3][4]. Plutella xylostella poses a significant threat to the foliage of vegetables during its larval period, with adults laying eggs on the fresh leaves, leading to significant economic losses due to diminished yields and compromised produce quality [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Landscape characteristics, such as landscape diversity, patch size and fragmentation, have an important impact on the insect pest dispersal capacity, pest population dynamics and size [39]. As landscape patterns in agroecosystems can vary in space and time, this can be reflected by altered distribution and pest abundance [40].…”
Section: Introductionmentioning
confidence: 99%